The effects of a semen cuscutae flavonoids-based antidepressant treatment on microbiome and metabolome in mice - Shao, Qianfeng; Zhou, Sheng; Li, Yue; Jin, Lin; Fu, Xiaowei; Liu, Tong; Wang, Jing; Du, Shaohui; Chen, Che (Frontiers in Microbiology, 2025)
BackgroundDepression is a prevalent psychiatric disorder and one of the leading causes of disability worldwide. Previous studies have shown that Semen Cuscutae flavonoids (SCFs) exert antidepressant effects by modulating the microbiota-neuroinflammation axis and ameliorating hippocampal metabolic disturbances. However, the impact of SCFs on gut microbiota and related metabolomics remains largely undefined. Given that the gut microbiota has been proven to play a significant role in the etiology of depression and serves as a promising target for its treatment in humans, this study aims to elucidate the antidepressant effects of SCFs and to investigate how they modulate microbial and metabolic pathways to alleviate depressive symptoms.Materials and methodsChronic unpredictable mild stress (CUMS)-induced mice were used as a depression model. The normal mice and CUMS-induced mice were treated with either vehicle or with SCFs. A range of standardized behavioral assays and physiological indicators were employed to evaluate the antidepressant effects of SCFs. Upon the confirmation of the effectiveness of the SCFs treatment, the composition, richness, and diversity of the fecal microbiota were assessed using 16S rRNA gene sequencing. Additionally, fecal metabolic profiling was analyzed using UHPLC-MS/MS-based metabolomics. Multivariate data analysis was subsequently performed to identify differential metabolites and characterize alterations in fecal metabolites. Furthermore, a correlation analysis between differential metabolites and key microbiota was conducted.ResultsSCFs significantly ameliorated depressive behaviors and the dysregulated diversity of fecal microbiota induced by CUMS. SCFs enhanced the gut microbiota structure in the CUMS group by increasing the Firmicutes/Bacteroidota ratio, significantly elevating the abundance of Firmicutes, Lactobacillus, Limosilactobacillus, and Actinobacteria while reducing the abundance of Bacteroidota and Bacteroides in CUMS-treated mice. Fecal metabolomics analyses revealed that SCFs could modulate metabolic pathways, including aldosterone synthesis and secretion, arachidonic acid metabolism, and primary bile acid biosynthesis.ConclusionsMice with depression induced by CUMS exhibited disturbances in both their gut microbiota and fecal metabolism. However, SCFs restored the balance of the microbial community and corrected metabolic disturbances in feces, exerting antidepressant effects through a multifaceted mechanism.